Robust, Superhydrophobic Aluminum Fins with Excellent Mechanical Durability and Self-Cleaning Ability - Wenbo Su; Xiangyou Lu; Yunxiang Shu; Xianshuang Liu; Wen Gao; Jianjie Yao; Zhuang Niu; Yuanlai Xie (Micromachines, 2023)
The self-cleaning ability of superhydrophobic metal surfaces has attracted extensive attention. The preparation of superhydrophobic material using the coating method is a common processing method. In this experiment, aluminum fins were processed by laser etching and perfluorinated two-step coating. The aluminum surface was modified using a femtosecond laser and 1H,1H,2H,2H- perfluorooctane triethoxysilane (PFOTES). A superhydrophobic aluminum surface with excellent mechanical stability and self-cleaning properties was obtained with the superhydrophobic contact angle (WCA) of 152.8° and the rolling angle (SA) of 0.6°. The results show that the superhydrophobic surface has an excellent cleaning effect compared with an ordinary surface in unit time. Then, a wear resistance test of the superhydrophobic surface was carried out by using the physical wear method. The results show that physical wear had a low influence on the hydrophobic property of the specimen surface. Finally, the Vickers hardness analysis found that the superhydrophobic surface hardness was significantly better than the ordinary surface hardness compared with the superhydrophobic surface hardness. Based on the excellent self-cleaning properties, wear resistance, and robustness of superhydrophobic materials, the laser-etched and perfluorinated superhydrophobic aluminum fins designed and manufactured in this study have broad application prospects in improving the heat transfer efficiency of finned heat exchangers.